Study of Sensory, Nutritional and Storability of Variants of Instant panjiri Mixes - Alpana Sharma, Suman Kumar and S.P. Mishra, (Indian Journal of Extension Education, 2018)
Panjiri, a traditional food product of Shahdol district and traditionally prepared from roasted wheat flour.Four variants of panjiri mixes incorporating different kinds of roasted legume dal flour viz., chickpea,green gram, soybean and field pea were prepared and evaluated on sensory, nutritional and storabilityparameters. Based upon the sensory evaluation, the optimized level of supplementation was found to be10% supplementation of roasted legume dal flour in roasted wheat flour. Soybean blended mix showedbetter nutritional quality in comparison to other mixes. Fortification of mixes with 10% skimmed milkpowder further enriched the products with higher contents of protein, calcium and phosphorus content. Theprepared instant panjiri mixes were monitored for changes in moisture content, free fatty acids as well assensory quality during storage and was found stable for 6 months at ambient conditions in polyethylenebags. The cost analysis of mixes showed that the cheapest products were based on soybean and fieldpeawhich had lower values in comparison to other products based on green gram and chickpea.